Molecular clock evidence for survival of Antarctic cyanobacteria (Oscillatoriales, Phormidium autumnale) from Paleozoic times - Strunecký, O. (Otakar); Elster, J. (Josef); Komárek, J. (Jiří) (FEMS Microbiology Ecology, 2012)
Cyanobacteria are well adapted to freezing and desication; they have been proposed as possible survivors of comprehensive Antarctic glaciations.We tested the hypothesis that cyanobacteria survived Antarctic glaciations directly on site after the Gondwana breakup by using the relaxed and strict molecular clock in the analysis of the 16S rRNA gene. We estimated that the biogeographic history of Antarctic cyanobacteria belonging to P. Autumnale lineages has ancient origins. The oldest go fruther back in time than the breakup of Gondwana and originated somewhere on the supercontinent between 442 and 297 Ma. Enhanced speciation rate was found around the time of the opening of the Drake Passage (c. 31-45 Ma) with beginning of glaciations (c.43 Ma.